Analysis of construction and demolition waste generation at Kuantan, Pahang - Advein, Ami (2017)
Construction waste is a growing problem in both developed and developing countries. Developing countries are moving towards better management of construction waste however there is still inadequate collection and improper disposal of construction waste. Construction waste broadly refers to waste arising from construction, demolition, renovation, property development, infrastructure construction, earthworks and land clearing operations (US EPA 1998, Tang, Soon & Larsen 2003). It consists of wood, concrete, metal, brick, drywall, roofing, packaging materials, plastic, paper, cardboard and others. In construction building, the usage of concrete, glass, steel, brick, aluminium, and plastics are commonly use in large quantities that can causes the waste to the materials.